Divination and philosophy in the letters of Paul - Sharp, Matthew T. (Edinburgh Studies in Religion in Antiquity, 2022)
Studies the topic of divine communication in Paul’s letters in the context of Graeco-Roman divinationProvides rigorous historical comparison of Paul with a range of Greek, Roman and Jewish sourcesCritiques conventional theological categories and prejudices that inhibit comparison between Paul and his historical contextCritiques one-sided treatments of divination that view it solely in terms of power relationsBrings together diverse topics such as prophecy, revelation, scriptural interpretation, anthropology and cosmology into a coherent whole through the lens of divinationThis book analyses the apostle Paul’s claims to receive and interpret knowledge from divine sources within the context of divination in the Graeco-Roman world. Each chapter studies a particular aspect of divination in Paul’s letters in comparison with similar phenomena in the Graeco-Roman world, dealing in turn with the underlying logic of divination (in the context of ancient philosophical conversations), visionary experience, prophecy and divine speech, the divinatory use of texts and the interpretation of signs. As such, the book forms an in-depth study of divine communication in Paul’s letters, integrating this theme with the broader topics of cosmology, anthropology, eschatology and theology.While New Testament texts and early Christian figures have traditionally been studied from the vantage point of theological categories (such as ‘revelation’) that isolate early Christianity from its historical context in the Graeco-Roman world, this book re-reads Paul’s thought and practice concerning divine communication within, not against, the Graeco-Roman thought and practice of divination. In doing so it illuminates the coherence and connections both between Paul and his historical context and between diverse topics of Paul’s letters that have usually been studied in isolation from each other